Pengaruh Media Wordwall terhadap Kemampuan Numerasi Siswa Kelas 1 SDN Plamongansari 02 Semarang - Dyah Kusumaningrum, Thessa; Lestyarini, Ikha; Nuvitalia, Duwi; Wikyuni, Sri (Melati Institute, 2024)
This study aims to examine the effect of using Wordwall educational media on improving student learning outcomes. This study used a quantitative method with a one-group pretest-posttest quasi-experiment design. The subjects were 25 first grade students at SD N Plamongansari 02 Semarang. Data analysis was conducted using normality test and paired sample t-test. The results showed that the average pretest score was 56.6 and the average posttest score was 82.4. Thus, there is an increase in pretest and posttest scores, showing a significant effect of Wordwall educational media on student numeracy skills in Mathematics subjects. This is evidenced by the significance value of 0.118; 0.130 ? 0.005.